Phosphorus fertilizer technology activated from phosphorus powder and mineralized mass - Nozimov, Ezozbek; Sultanov , Bohodir; Kholmatov , Dilshod; Sherkuziev , Doniyor; Nodirov , Alisher (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents the results of obtaining activated phosphorous fertilizer (APF) using phosphoric acid extraction (PAE) from phosphorite powder (PP), which is formed during the washing processes of Central Kyzylkum (CK) phosphorites at high temperature enrichment. Phosphoric acid containing 18.0-21.0% P2O5 and its standards of 110-120% were found to be acceptable sizes for experiments. The main components of APF received in these sizes are as follows: Total P2O5. 30.75-31.53%; P2O5 - 16.28-18.30%; P2O5s.w.- 4.46-5.30%; CaO comm.– 22.33-22.79%; CaO assim. – 12.20-13.18% (when using PP) and total P2O5.-32.58-33.15%; P2O5 - 17.26-19.23%; P2O5s.w.- 4.49-5.39%; CaOcomm.-29.13-29.31%; CaOassim.-15.67-17.22% (when using MM).